Novel monoclonal antibody L2A5 specifically targeting sialyl-Tn and short glycans terminated by alpha-2–6 sialic acids - Loureiro, Liliana R. (2018)
This work was supported by the Bluepharma innovation award "Trifunctional antibodies and dendritic cell-based technologies: a combined approach to cancer immunotherapy" 2013 and the Scientific merit prize Santander - Totta - Lisbon New University - "Antibody engineering for breast cancer therapy" 2013. LRL is supported by the grant PD/BD/52476/2013 from the Portuguese Foundation for Science and Technology (FCT). The work is partially supported by FCT-MCTES through the grants IF/00033/2012 (ASP), SFRH/BPD/101827/2014 (LL) and SFRH/BPD/111048/2015 (JAF), the Wellcome Trust Biomedical Resource grant (WC) and the NSFC-Shandong Joint Fund (U1606403) (CL). The authors also acknowledge FCT funding for CI-IPOP research unit (PEst-OE/SAU/UI0776/201). co-financed by the European Regional Development Fund under the PT2020 Partnership Agreement (POCI-01-0145-FEDER-007728). FCT is co-financed by European Social Fund (ESF) under Human Potential Operation Programme (POPH) from National Strategic Reference Framework (NSRF). The funders did not play a role in the study design, data collection or decision to publish.